A Left-inverse Non-linear Controller to a RRR Manipulator - Lopes, Igor; Dias, Samaherni; Queiroz, Kurios (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2020)
This paper considers the control of an articulated robotic manipulator, classified in the literature as anthropomorphic (RRR), which is formed by three rotary joints, three degrees of freedom, and spatial movement. This kind of manipulator provides large freedom of movement inside its workspace and it is widely used in many fields. In order to control the manipulator, a PD control strategy will be used, which makes use of an inversion of systems to decouple and control each joint individually. In the end, to verify its behavior, the proposed controller is simulated.